(untitled) (New York, 1997)
The readings in the Adventures in time and Place Anthology have been carefully selected to enhance social studies concepts and to provide enjoyable and worthwhile reading experiences for students.
Keywords: United States,Hoa Kỳ; History,Lịch sử